Ketahanan Beberapa Genotipe Jagung Hibrida Umur Genjah terhadap Sitophilus zeamais Motschulsky - ,, suriani; Tenrirawe, Andi; Makkulawu, dan Andi Takdir (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Sitophilus zeamais is a major pest of cereal products in the storage that can reduce the quality and quantity of the grain. The use of resistant variety is an efficient method to control S. zeamais. This research aimed to evaluate the resistance of 8 early maturing hybrid maize genotypes to S. zeamais. The research was arranged in a single factor completely randomized design with 3 replications, involving 8 genotypes and 4 check varieties. Samples of 25 g seeds were stored in the container covered by gauze, then infested with same-aged 5 males and 5 females of S. zeamais and maintened to 105 days. Observed variables were the number of F1 progenies of S. zeamays, susceptibility index, seed damage, and weight loss. Based on the results, 3 early maturing hybrid maize genotypes (CH-19, CH-18 and CH-20) exhibited high resistance to the S. zeamais as indicated by their susceptibility index, number of progenies, percentage of seed damage, and weight loss. These genotypes had susceptibility index of 1.23-1.80 with low percentage of seed damage of 2.07-4.55%. Correlation tests showed that the susceptibility index of maize seeds had positive correlation with number of progenies and seed damage.Keywords: seed, stored pest, susceptibility index